Death note : Contact / 9 - Oba, Tsugumi (Deathnote, 2007)
"Light has always been confident in his ability to outthink everyone, but L's proteges are proving to be more of a challenge than he anticipated. The more Light mentally maneuvers, the tighter the net around him becomes. And now Near and Mello are working to break the taskforce apart and expose Kira from within!".